Jaw claudication is the only clinical predictor of giant-cell arteritis. Issue 3 (May 2017) - Sato, Hitoshi; Inoue, Mariko; Muraoka, Wataru; Kamatani, Takaaki; Asoda, Seiji; Kawana, Hiromasa; Nakagawa, Taneaki; Wajima, Koichi
Abstract: Giant-cell arteritis (GCA), commonly known as temporal arteritis, is a chronic granulomatous vasculitis that affects predominantly the extracranial branches of the carotid artery. Although an algorithm for diagnosing GCA that includes both biopsy and imaging examinations has been recently proposed, it harbors the possibility of false negatives. Hence, jaw claudication caused by ischemia of the masticatory muscles is one of the important clinical predictors for implementation of temporal artery biopsy (TAB). We describe a case of GCA in which jaw claudication was the only clinical predictor for implementation of TAB. A 78-year-old man was referred to our department with facial pain associated with mastication. He had been admitted 3 weeks previously to another department to investigate an unidentified fever. A blood test revealed an elevated C-reactive protein level and a high erythrocyte sedimentation rate (70 mm/h). Although ultrasonography and computed tomography angiography of the temporal region showed no findings specific for GCA, based on our examinations we determined that his facial pain arose from jaw claudication rather than temporomandibular disorder. Histopathological examination by temporal artery biopsy showed intima thickening with disruption of elastic lamina and inflammatory cell infiltration, and we consequently diagnosed GCA. Clinical symptoms immediately resolved after prescription of prednisolone 40 mg/day for 2 days. In this case of GCA the imaging examinations of the superficial temporal artery were false-negative, and jaw claudication was the most important predictor of GCA.